Leadership games experiential learning for organizational development - Kaagan, Stephen S.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Leadership Games presents 25 practical activities designed to be used in various leadership training and development programmes. Each exercise includes a set of directions giving advice on strategy, appropriate timing, and questions to use at the end.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Leadership; Management games; Employees -- Training of; Experiential learning; Electronic books